L’Europa della cultura di Friedrich Nietzsche - Erminio Maglione (Rosenberg & Sellier, 2015)
This article’s primary goal is enlightening, through the interpretation of salient passages from his work, how Europagedanke completely innervates Nietzsche’s production, assuming the particular form of physiological poetics. This last one, that is the surgical enucleation of contemporary man’s symptoms of décadence, could indicate the European citizen’s ideal aim too: a cultural communion able to preserve the differences against every nationalism.